Kreativitas Mahasiswa dalam Struktur Content Peta Konsep pada Pembelajaran Biologi Sel - Tresnawati, Cita; Utari, Toto Sutarto Gani (Bioedukasi: Jurnal Pendidikan Biologi, 2020)
One of the learning  characteristic in 21st century is demanding the student  ability to think creative therefore hopefully can survive in the  global competition creativity can produce products the  innovative, original and update products. Therefore the products can be maximal useful and has better quality. This research  has purpose to analyze student creativity in content structure map concept on cell bology learning. We used the method of descriptive with the quantitative approaching that involved 32 students. The resesarch is doing on odd semester. With the subject of the semester III student research who took the cell biology subject. The instruments are : 1) paper of creativity evaluation that get from  student assignment documentation and,  2) peper of student performance when they have presentation. The result of research showed that student creativty with the averange mark 3,24 on the best category. This show that student can plan, design, and make structure map concept like identified from the student ability in deciding, identifying, designing, connecting, mixing, making idea and presenting the result of map concept that can produce creative ideas with the good creativity result product, so it can answer the problem of concept control in biology learning. The result of student performance assessment in presesnting the result of map concept shows the ability on good category. This is identified on the ability of telling the idea and thougt and concept controlKeywords: Creativity, Cell Biology Learning, Content Structure Map Concept